The journalist in research and art - Marocco, Beatriz (Brazilian journalism research, 2013)
The journalist has been the subject of arts and sciences. By this insertion in the theme of the panel “Settings and perspectives of journalism research in Brazil in dialogue with Latin American studies in journalism”, held at the meeting of Brazilian Association of Journalism Researchers, SBPJor (Curitiba, November 10th 2012) I recognized that the academic sphere outlines two types of action: network researching in different countries and regions of the world, with the participation of Latin American countries in collaborative research; and research projects with other collaboration bases. Both modalities dialogue with the production of movies and literature – which makes visible the professional’s great power for plots and tensions.